INTERACTION OF DOXORUBICIN WITH DNA-HMG1 COMPLEX (Journal of Sciences, Islamic Republic of Iran)
In this study, the interaction of the anthracycline antibiotic doxorubicin with DNA-HMG 1 complex was investigated employing UV/VIS spectroscopy, thermal denaturation and DNA cellulose chromatography techniques. The results indicated that the binding of doxorubicin to the protein reduces its Tm in a dose dependent manner. Although doxorubicin protects free DNA against thermal denaturation in the presence of HMG 1, thermal melts represent biphasic profile corresponding to DNA- drug, HMG1- drug and free components. Interaction of antibiotic with DNA - HMGl complex using DNA cellulose columns also implies that the drug binds strongly to singlestranded DNA-HMG 1 complex rather than to double- stranded DNA-HMG 1 columns. The results suggest destabilization of HMGl protein by drug action thereby preventing DNA-HMG 1 complex formation